Analisis Potensi Likuifaksi Akibat Gempa (Studi Kasus : Reklamasi Pelabuhan Kontainer Belawan Fase-2) - HUTAGALUNG, Mario; TARIGAN, Simon Dertha (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
One of the impacts caused by an earthquake is the strength loss of the soil due to cyclic stresses calledliquefaction. Liquifaction usually occurs in loose sand. The objective of this study is to determine thepotential of liquefaction in observed project. The project observed in this study is reclamation project.Analysis for potential liquefaction is done using the Simplified Procedure Method. Firstly, determinethe value of peak acceleration in bedrock in the study area based on the 2010 Indonesian EarthquakeHazard Map. Secondly, collect soil data based on CPT-u testing. Based on these data, the accelerationvalue (Amplification/Deamplification) can be found on each soil layer when being moved from thebedrock to the ground surface. By comparing the average shear stress caused by the acceleration ofthe earthquake to the effective vertical stress at each soil layer, we can obtain the value of CyclicStress Ratio. Lastly, calculate CRR (Cyclic Resistant Ratio) which is the value of soil resistance toliquefaction. Based on CRR value, it can be seen the corrected conus penetration value (qc1N). Thethree parameters are then connected in the NCEER 1996 chart to assess which soil layers arepotentially liquefied or not during an earthquake.